(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Smart-home researchers’ opinions and experiences suggest that privacy and choice are their main ethical concern. The researchers consider the private life of a person as a major problem when conducting research, though tending to see privacy in terms of information privacy, seldom see privacy as a personal privacy. In addition, we urge smart house-researchers to focus upon this. These are two major ethical issues. Is it necessary to concentrate on privacy? While some sort of privacy respect is a global social norm, it is fundamentally debated whether and when privacy is considered to be a moral principle coherently, as respect for privacy specifically limits the application of other moral requirements. Maybe due to the disputed moral significance, privacy-based moral arguments are at the forefront of many polarised bioethic discussions. Philosophical debates on privacy concentrate whether privacy is in the interests of one’s own right (and therefore vulnerable to harm) or a cluster of other more fundamental interests, such as ownership and freedom interests.